Students’ knowledge on the identification and use of physics laboratory apparatus in post-basic schools in Ilorin, Nigeria - Wasiu Olayinka Yahaya; Abdulrasaq Oladimeji Akanbi (Universitas Majalengka, 2023)
Physics teaching and learning theoretically may not achieve its full objectives without the integration of laboratory activities. The study measures post-basic school students’ knowledge of identification and use of physics laboratory apparatus so as to ascertain their readiness for external examinations. The method adopted was descriptive survey of cross sectional type of research that enables data collection through measurement tool. One hundred and forty-three physics students’ check-lists were analysed using descriptive statistics (frequency count and simple percentage). The findings of this study revealed that out of the commonly identified physics laboratory apparatus, students high strength was recorded in identifying the apparatus like retort stand, weight/mass, meter rule, pendulum bob, knife edge, optical pin, glass prism and test tube. The students show high strength in stating correct use of the apparatus like meter rule, stop watch, beaker, ammeter and voltmeter. It is recommended that pasting and displaying the apparatus pictures, name of the apparatus, its uses/functions beside it in the physics laboratory wall and early exposure of the students to laboratory activities will help the students in apparatus identification and prepare them for external examinations.